The Welfare Cost of Imperfect Competition and Distortionary Taxation - Magnus Jonsson (Sveriges Riksbank, 2004)
The welfare cost of imperfect competition in the product and labor market as well as distortionary taxation is quantified in a dynamic general equilibrium model parameterized to fit the U.S. economy. We find that the welfare cost of imperfect competition in the product market is 35.74 percent while it is 0.66 percent in the labor market, taking the transition from the distorted to the optimal steady state into account. If we also take into account that the U.S. economy is characterized by distortionary taxation the welfare cost in the product market increases to 48.26 percent and 4.70 percent in the labor market.
Keywords: D40; H20; L10; 330; monopolistic competition; distortionary taxation; welfare